Heterogeneidades - Barros, Ev’Angela Batista Rodrigues de; Campello, Priscila Campolina de Sá; Guimarães, Raquel Beatriz Junqueira; Cavalcante, Sandra Maria Silva (Scripta, 2018)
Apresentação do volume.